Development of Asoka-Based Smart Pedagogy Edukit to Strengthen TPACK of Automotive PPG Students in the Student Understanding and Learning Course - Dani Irawan; M. Anas Tohir; Muhammad Alfan; Ahmad; Putri Dwi Kartini; Nia Arlika (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This research is motivated by the suboptimal Technological Pedagogical Content Knowledge (TPACK) competency of PPG automotive study students in designing meaningful, contextual learning that is in accordance with the characteristics of vocational high school students. The results of the needs analysis indicate that the teaching materials in the Student Understanding and Learning course are still generic and have not integrated the automotive vocational context, reflective learning experiences, and the systematic use of learning technology. This condition has an impact on the tendency of students to be oriented towards the administrative fulfillment of learning devices without in-depth pedagogical design. Therefore, an innovative product-based learning device that is implementable is needed to facilitate the strengthening of TPACK in an integrated manner. This study aims to: (1) develop an ASOKA-based Smart Pedagogy Edukit that is contextual to automotive vocational learning; (2) analyze the level of validity and practicality of the product; and (3) test the effectiveness of edukit in improving PPG students' TPACK competency in designing meaningful and reflective learning. The study used a mixed method approach with the ADDIE development model which includes the stages of needs analysis, product design, development through expert validation and limited trials, implementation using quasi-experiments, and evaluation for product refinement. Data collection was carried out through questionnaires, interviews, observations, assessment of learning tools, and documentation, with descriptive statistical analysis, Aiken's V, MANOVA, and qualitative analysis assisted by NVivo. The results of the study indicate that the ASOKA-based Edukit Smart Pedagogy was successfully developed as a learning tool that integrates pedagogical competencies, vocational content, and technology to strengthen the TPACK competencies of Automotive PPG students. The resulting product includes an implementation guide, learning modules, automotive case studies, interactive digital media, TPACK instruments, pedagogical reflection sheets, and is integrated with the Learning Management System (LMS). The results of expert validation show that the product is categorized as very valid, while the practicality test received very positive responses from lecturers and students. Product implementation is proven to increase learning engagement, pedagogical reflection skills, and student TPACK competencies compared to conventional learning.time, thus supporting data-based learning decision making.